(untitled) (Medico Legal Update, 2020)
Background: Exclusive breastfeeding for six months is an effort to increase the breastfeeding benefits and reduce infant mortality rate. Self efficacy is one of the factors that can influence the level of confidence exclusive in breastfeeding. Aim: This study aimed to identify the level of self efficacy before and after given modified buzz group method and to the influence of modified buzz group method about exclusive breastfeeding against self efficacy in pregnant mother Method: This study was designed using quasi-experimental design. The study was conducted in the working area of the health center. The total population used in this study was 42 pregnant women. A total sample of 38 respondents was taken according to purposive sampling. BSES-SF (Breastfeeding Self Efficacy Scale Short Form) questionnaire was administered at pre-test and post-test. Data analysis was performed using the Wilcoxon Signed Rank test and the Mann Whitney test. Results: The results showed that the Wilcoxon Signed Rank statistical test obtained p value of 0,000 in the treatment group and p value of 0.355 in the control group. The Mann Whitney statistical test obtained a significant value of p = 0,000 at the post-test. The modification of the buzz group method took effect to increased self efficacy about exclusive breastfeeding for pregnant mother because this method was organized by four sources of self efficacy that was direct experience, indirect experience, verbal persuasion, and emotional condition. Conclusion: With the modification of the buzz group method and self efficacy for pregnant mother can increase of value for breastfeeding exclusive coverage.